Comparison of multiple electrode aggregometry with lumi‐aggregometry for the diagnosis of patients with mild bleeding disorders. (13th September 2017) - Al Ghaithi, R.; Drake, S.; Watson, S. P.; Morgan, N. V.; Harrison, P.
Abstract : Essentials There is a clinical need for new technologies to measure platelet function in whole blood. Mild bleeding disorders were evaluated using multiple electrode aggregometry (MEA). MEA is insensitive at detecting patients with mild platelet function and secretion defects. More studies are required to investigate MEA in patients with a defined set of platelet disorders. Summary: Background: Multiple electrode aggregometry (MEA) measures changes in electrical impedance caused by platelet aggregation in whole blood. This approach is faster, more convenient and offers the advantage over light transmission aggregometry (LTA) of assessing platelet function in whole blood and reducing preanalytical errors associated with preparation of platelet‐rich plasma (PRP). Several studies indicate the utility of this method in assessing platelet inhibition in individuals taking antiplatelet agents (e.g. aspirin and clopidogrel). Objective: Our current study sought to evaluate the ability of MEA in diagnosing patients with mild bleeding disorders by comparison with light transmission lumi‐aggregometry (lumi‐LTA). Methods: Forty healthy subjects and 109 patients with a clinical diagnosis of a mild bleeding disorder were recruited into the UK Genotyping and Phenotyping of Platelets study (GAPP, ISRCTN 77951167). MEA was performed on whole blood using one or two concentrations of ADP, PAR‐1 peptide, arachidonic acid and collagen. Lumi‐LTA was performed in PRP using several concentrations of ADP, adrenaline, arachidonic acid, collagen, PAR‐1 peptide and ristocetin. Results: Of 109 patients tested, 54 (49%) patients gave abnormal responses by lumi‐LTA to one or more agonists. In contrast, only 16 (15%) patients were shown to have abnormal responses to one or more agonists by MEA. Conclusions: In this study we showed that MEA is less sensitive in identifying patients with abnormal platelet function relative to lumi‐LTA.